2017
DOI: 10.1186/s12896-016-0321-6
|View full text |Cite
|
Sign up to set email alerts
|

Multi-antigen avian influenza a (H7N9) virus-like particles: particulate characterizations and immunogenicity evaluation in murine and avian models

Abstract: BackgroundHuman infection with avian influenza A virus (H7N9) was first reported in China in March 2013. Since then, hundreds of cases have been confirmed showing severe symptoms with a high mortality rate. The virus was transmitted from avian species to humans and has spread to many neighboring areas, raising serious concerns over its pandemic potential. Towards containing the disease, the goal of this study is to prepare a virus-like particle (VLP) that consists of hemagglutinin (HA), neuraminidase (NA) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 31 publications
(31 reference statements)
2
24
1
Order By: Relevance
“…Notably, our synthetic H7-VLP exhibited a haemagglutination activity at a minimum total protein amount of 0.01 μg (Fig. 5 b), which is lower than the minimum total protein amount of H7 VLP exhibiting haemagglutination activity from previous studies of Hu et al [ 9 ] and Pushko et al [ 23 ] of 0.098 and 0.039 μg, respectively. In contrast, in the present study, the free trimeric H7 agglutinated chicken RBCs at a minimum amount of total protein of 5 μg.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Notably, our synthetic H7-VLP exhibited a haemagglutination activity at a minimum total protein amount of 0.01 μg (Fig. 5 b), which is lower than the minimum total protein amount of H7 VLP exhibiting haemagglutination activity from previous studies of Hu et al [ 9 ] and Pushko et al [ 23 ] of 0.098 and 0.039 μg, respectively. In contrast, in the present study, the free trimeric H7 agglutinated chicken RBCs at a minimum amount of total protein of 5 μg.…”
Section: Discussioncontrasting
confidence: 66%
“…The H7-VLPs vaccine has been shown to elicit highly efficient and protective immune responses against the H7N9 influenza virus because of high molecular weight of H7 formation, which was formed by its self-assembly [ 9 , 21 , 23 ]. According to previous studies on the efficacy of neutralizing antibodies elicited by recombinant HA proteins from avian H5N1 influenza virus, a high-molecular-weight HA oligomer elicited the strongest neutralizing antibody response, followed by the HA trimer, while the monomer showed minimal efficacy [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that live attenuated A(H7N9) vaccine, inactivated cell-cultured whole-virus A(H7N9) vaccine, and virus-like particles bearing HA, NA, and M1 of A(H7N9) virus all induce significant N9 antibody titers in animal models (45)(46)(47). The contribution of NA immunity in ameliorating human A(H7N9) infections deserves further investigation in order to improve A(H7N9) vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Although synthetically prepared nanoparticles have yet to show the level of ordered antigen arrangement found on viruses and virus-like particles derived from cell culture systems [181,182], ongoing studies continue to demonstrate emerging techniques to couple antigens of interest to nanocarriers. In the last section of the review, we review commonly used methods for coupling antigens with nanoparticles.…”
Section: Repetitive Antigen Display For Immune Activationmentioning
confidence: 99%